27-Hydroxycholesterol/liver X receptor/apolipoprotein E mediates zearalenone-induced intestinal immunosuppression: A key target potentially linking zearalenone and cancer - Haonan Ruan; Jing Zhang; Yunyun Wang; Ying Huang; Jiashuo Wu; Chunjiao He; Tongwei Ke; Jiaoyang Luo; Meihua Yang (Elsevier, 2024)
Zearalenone (ZEN) is a mycotoxin that extensively contaminates food and feed, posing a significant threat to public health. However, the mechanisms behind ZEN-induced intestinal immunotoxicity remain unclear. In this study, Sprague-Dawley (SD) rats were exposed to ZEN at a dosage of 5 mg/kg/day b.w. for a duration of 14 days. The results demonstrated that ZEN exposure led to notable pathological alterations and immunosuppression within the intestine. Furthermore, ZEN exposure caused a significant reduction in the levels of apolipoprotein E (ApoE) and liver X receptor (LXR) (P < 0.05). Conversely, it upregulated the levels of myeloid-derived suppressor cells (MDSCs) markers (P < 0.05) and decreased the presence of 27-hydroxycholesterol (27-HC) in the intestine (P < 0.05). It was observed that ApoE or LXR agonists were able to mitigate the immunosuppressive effects induced by ZEN. Additionally, a bioinformatics analysis highlighted that the downregulation of ApoE might elevate the susceptibility to colorectal, breast, and lung cancers. These findings underscore the crucial role of the 27-HC/LXR/ApoE axis disruption in ZEN-induced MDSCs proliferation and subsequent inhibition of T lymphocyte activation within the rat intestine. Notably, ApoE may emerge as a pivotal target linking ZEN exposure to cancer development.